2020
DOI: 10.1177/0300060520934627
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cyclosporin A pre-treatment combined with etomidate post-treatment on lung injury induced by limb ischemia-reperfusion in rats

Abstract: Objectives To investigate the influence of cyclosporin A (CsA) pre-treatment and etomidate (ETO) post-treatment on lung injury induced by limb ischemia-reperfusion (I/R) in rats. Methods Rats were randomly divided into five groups: sham, I/R, I/R+CsA, I/R+ETO, and I/R+CsA+ETO. Limb I/R lung injury was established by bilateral clamping of the femoral arteries for 2 hours. Following reperfusion for 3 hours, blood gas analysis was performed. Pathological changes were assessed using immunohistochemistry. The apopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Our previous studies indicated curcumin post-conditioning could play a protective role in the lung injuries induced by limb I/R via inhibiting the TRL4/NF-κB p65 pathway. 11 Our previous research results also showed similar protective effects in the rat kidney, as assessed using the matrix metalloproteinase (MMP)-9/ tissue inhibitors of metalloproteinase (TIMP)-1 ratio during the process of limb I/R, 12 but the protective effects in the rat lung via the Notch2/Hes-1 signal pathway were not reported. In our experiment, inflammatory cell infiltration, alveolar septum thickening, alveolar interstitial congestion and edema, and occasional localized atelectasis were observed in the lung HE pathology section in the I/R group.…”
Section: Discussionmentioning
confidence: 77%
“…Our previous studies indicated curcumin post-conditioning could play a protective role in the lung injuries induced by limb I/R via inhibiting the TRL4/NF-κB p65 pathway. 11 Our previous research results also showed similar protective effects in the rat kidney, as assessed using the matrix metalloproteinase (MMP)-9/ tissue inhibitors of metalloproteinase (TIMP)-1 ratio during the process of limb I/R, 12 but the protective effects in the rat lung via the Notch2/Hes-1 signal pathway were not reported. In our experiment, inflammatory cell infiltration, alveolar septum thickening, alveolar interstitial congestion and edema, and occasional localized atelectasis were observed in the lung HE pathology section in the I/R group.…”
Section: Discussionmentioning
confidence: 77%
“…The pretreatment protocol design is widely used in the field of solid organ transplantation and pathologies involving uncontrolled production of circulating inflammatory cells. Immunosuppressants, such as calcineurin inhibitors, have been used as a pretreatment in several models of ALI (15,16) and in the field of transplantation (29,30). Our experimental protocol evaluating therapeutic intervention with tacrolimus as a pretreatment before brain death is the first step to highlight the potential therapeutic use of tacrolimus in lung allograft preservation in the condition but requires further study in a more clinically translational way after declaration of brain death.…”
Section: Discussionmentioning
confidence: 99%
“…Tacrolimus, a macrolide immunosuppressant belonging to the calcineurin inhibitor family, modulates the cellular immune and nonimmune mechanisms responsible for acute lung graft rejection, such as reduced pulmonary capillary leakage and decreased leukocyte infiltration, as well as the altered release of proinflammatory cytokines (12)(13)(14). Interestingly, calcineurin inhibitors have already been used successfully as a pretreatment in several models of acute lung injury (ALI) (15)(16)(17)(18), but never in brain death-induced lung injury.…”
mentioning
confidence: 99%
“…However, after the ischaemia-reperfusion of tissues and organs, the injury does not stop and it may be further aggravated. 1 Organs with an abundant blood supply can even experience two phases of pathological damage. Research has shown that pulmonary injury induced by limb ischaemia-reperfusion is a complex process involving multiple signalling pathways and factors.…”
Section: Introductionmentioning
confidence: 99%